TRAINING NEEDS ANALYSIS FOR NEW EMPLOYEE AT CLASS IIB BREBES PRISON - Rifaldi, Ading; Rifani, Dennny Nazaria (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Human resources are an important asset in correctional institutions, where correctional institutions play a role ranging from providing security to guiding prisoners. However, the training received, especially by new employees, is still very minimal, resulting in skill degradation and less than optimal guidance. This study aims to identify the current skills and skill needs so that any lack of skills is identified in new employees. The study used a qualitative method by conducting interviews with 8 new employees recruited in 2019 and 2021 and the Head of Administration, and by conducting document studies. This study uses the Training Needs Analysis theory by conducting organizational analysis, task analysis, and individual analysis. The results of this study can illustrate that new employees still do not have the skills needed to carry out their duties as correctional officers. This is due to the lack of training received by new employees. So, several organizational goals have not been optimally implemented. Therefore, new employees need to get training according to their fields so that they can carry out their duties optimally and organizational goals can be achieved optimally. Keywords: Training Needs Analysis; New Employees; Prison